-5(16.5+3t)=3(9-t)

Simple and best practice solution for -5(16.5+3t)=3(9-t) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(16.5+3t)=3(9-t) equation:


Simplifying
-5(16.5 + 3t) = 3(9 + -1t)
(16.5 * -5 + 3t * -5) = 3(9 + -1t)
(-82.5 + -15t) = 3(9 + -1t)
-82.5 + -15t = (9 * 3 + -1t * 3)
-82.5 + -15t = (27 + -3t)

Solving
-82.5 + -15t = 27 + -3t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '3t' to each side of the equation.
-82.5 + -15t + 3t = 27 + -3t + 3t

Combine like terms: -15t + 3t = -12t
-82.5 + -12t = 27 + -3t + 3t

Combine like terms: -3t + 3t = 0
-82.5 + -12t = 27 + 0
-82.5 + -12t = 27

Add '82.5' to each side of the equation.
-82.5 + 82.5 + -12t = 27 + 82.5

Combine like terms: -82.5 + 82.5 = 0.0
0.0 + -12t = 27 + 82.5
-12t = 27 + 82.5

Combine like terms: 27 + 82.5 = 109.5
-12t = 109.5

Divide each side by '-12'.
t = -9.125

Simplifying
t = -9.125

See similar equations:

| 37-7r=4-8(1+7r) | | -3(2x+6)+6(6x+5)=42 | | -2=v+2-5v | | 39x+132-31=38243 | | 4x+2=1x+4 | | (-4)*(-4)*(-4)*(1)= | | 32=w | | 5+16x=-59 | | 16=10m-14 | | 2+4(x+2)=7(x+1)-9 | | 5(6x+2)+4(1-4x)=14 | | 4x^5-4x= | | 45.49=n/2+5 | | 8v-4(v-8)=8 | | 14x-9x-11+17=-3x+78 | | 6(3a+1)-30=8(2a-4) | | 2x-2=3X+8 | | 39x+4(1413-981)=187367 | | -28=-2(n+5)-(-6n+6) | | 5Z=1.50 | | 0.80x+.05(2-x)=.10(76) | | 3(x-2y)= | | 6/8=x | | 5XZ=1.50 | | 3x-(11)=34+2x | | -2-(3-5t)= | | 8x=4(7x+25) | | 2=2(k+3)+4(5-2k) | | (6+2i)(-4-3i)= | | 5x+4=10-x | | -20=-4a-6a | | 3/4(24-8b)=3(5b+1) |

Equations solver categories